CCR4+ Skin-Tropic Phenotype as a Feature of Central Memory CD8+ T Cells in Healthy Subjects and Psoriasis Patients - Casciano, Fabio; Diani, Marco; Altomare, Andrea; Granucci, Francesca; Secchiero, Paola; Banfi, Giuseppe; Reali, Eva (Frontiers in Immunology, 2020)
The chemokine receptor CCR4 has emerged as a skin-homing molecule important for the migration of T cells from the blood to the dermis. From our previous data on psoriasis patients, CCR4+ memory T cells emerged as a putative recirculating population between skin and blood. Here we focused our attention on the expression of CCR4 and skin-tropic molecules in the different stages of memory T cell differentiation. We analyzed the chemokine receptor profile in CD8+ and CD4+ CD45RA−CCR7+ (TCM) and CD45RA−CCR7− (TEM) cells. Subpopulations were further divided on the basis of CD62L expression, and the distribution among the subsets of the skin-homing molecule CLA (Cutaneous Lymphocyte Antigen) was evaluated. The characterization was performed on peripheral blood mononuclear cells isolated from 21 healthy subjects and 24 psoriasis patients. The results indicate that (i) the skin-homing CCR4 marker is mainly expressed in TCM cells, (ii) CCR4+ TCM cells also express high level of CLA and that (iii) the more differentiated phenotype TEM expresses CXCR3 and CCR5 but lower level of CCR4 and CLA. This indicates that progressive stages of memory T cell differentiation have profoundly different chemokine receptor patterns, with CD8+ TCM displaying a marked skin-tropic phenotype CLA+CCR4+. Differential skin-tropic phenotype between TCM and TEM cells was observed in both healthy subjects and psoriasis patients. However, patients showed an expanded circulating population of CD8+ TCM cells with phenotype CCR4+CXCR3+ that could play a role in the pathophysiology of psoriasis and possibly in disease recurrence.